2020
DOI: 10.3389/fonc.2020.00389
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Class of Long Non-coding RNA With Oncogenic Role Arises From the snoRNA Host Genes

Abstract: The small nucleolar RNA host genes (SNHGs) are a group of long non-coding RNAs, which are reported in many studies as being overexpressed in various cancers. With very few exceptions, the SNHGs (SNHG1, SNHG3, SNHG5, SNHG6, SNHG7, SNHG12, SNHG15, SNHG16, SNHG20) are recognized as inducing increased proliferation, cell cycle progression, invasion, and metastasis of cancer cells, which makes this class of transcripts a viable biomarker for cancer development and aggressiveness. Through our literature research, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 207 publications
(195 reference statements)
6
112
1
Order By: Relevance
“…Nanoparticle-based small ncRNA vectors are the most common strategy [ 89 ]. SNHG3 is located in the nucleus and cytoplasm and requires a carrier to transport antisense RNAs or siRNAs into the cell to function [ 90 ]. Therefore, through continuous progress of antisense RNA or siRNA and ncRNA vectors, direct silencing of SNHG3 has become an important and powerful new target for tumor treatment.…”
Section: Perspectives In Clinical Practicementioning
confidence: 99%
“…Nanoparticle-based small ncRNA vectors are the most common strategy [ 89 ]. SNHG3 is located in the nucleus and cytoplasm and requires a carrier to transport antisense RNAs or siRNAs into the cell to function [ 90 ]. Therefore, through continuous progress of antisense RNA or siRNA and ncRNA vectors, direct silencing of SNHG3 has become an important and powerful new target for tumor treatment.…”
Section: Perspectives In Clinical Practicementioning
confidence: 99%
“…The oncogenic role of SNHGs in diverse human cancers is supported by solid scientific data, which show that they are related to stimulation of the following malignant processes: epithelial to mesenchymal transition, invasion, proliferation, cell cycle, and apoptosis evasion. 9 We intended to test the SNHGs expression and determined their clinical implication in AML. In this study, we for the first time revealed clinical implications of SNHGs expression in AML.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Small nucleolar RNA host gene (SNHG) family members (SNHGs) including SNHG1, SNHG2/GAS5, SNHG3, SNHG4, SNHG5, SNHG6, SNHG7, SNHG8, SNHG9, SNHG10, SNHG11, SNHG12, SNHG13/DANCR, SNHG15, SNHG17, SNHG20 and SNHG28, are newly recognized lncRNAs, which have been revealed to be oncogenes in several cancers. 9 Also, several members of SNHG family including SNHG1, SNHG3, and SNHG5 have been found to be dysregulated and play a crucial role in leukemogenesis, and also have prognostic value in AML. [10][11][12][13][14] Since little studies investigated the expression and clinical implications of SNHGs in AML, we systemically determined the prognostic role of SNHGs expression in patients with AML.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patient care management remains an important clinical challenge due to the lack of availability of prognostic markers that could stratify a patient’s risk. In the past few years, there has been an increased interest in verifying the clinical utility of coding and noncoding genes as important biomarkers for prognostic, diagnostic, and therapeutic targets [ 2 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%